Applying the Problem-Driven Iterative Adaptation (PDIA) Approach to Address Teacher Absenteeism and Improve Early Childhood Learning Quality in Pegunungan Arfak, West Papua - Nursalim; Pria Santri Beringin; Yeni Witdianti; Firman; Muhammad Akbar Hidayat (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
Teacher absenteeism remains a major challenge in remote and underdeveloped regions of Indonesia, particularly in the highlands of West Papua. The phenomenon has significant implications for the quality of early childhood and primary education. Drawing on findings from the Strategic Action Workshop on Reducing Teacher Absenteeism held in Pegunungan Arfak (UNIMUDA–UNICEF Partnership, 2025), this study analyzes the effectiveness of the Problem-Driven Iterative Adaptation (PDIA) approach in identifying root causes and designing locally relevant solutions. Using qualitative descriptive methods, data were collected through Gallery Walk observations, focus group discussions, and iterative reflections with participants. Results show that teacher absenteeism in Pegunungan Arfak is influenced by geographic inaccessibility, socio-cultural norms, and weak institutional coordination between education authorities and customary leaders. The most significant outcome of the PDIA process was the increase in teacher attendance that emerged after participants co-created feasible actions rooted in local conditions. Through PDIA, participants developed solutions such as customary education forums, teacher support groups, and community-based monitoring systems. This study offers practical guidance for district officials, school leaders, and community stakeholders seeking to strengthen accountability and improve learning continuity in remote education settings.